Collection of information about publicly traded firms - Bhushan, Ravi (Journal of Accounting and Economics, 1989)
This paper develops a model of information collection about publicly traded firms in an economy. The supply noise is modeled as the variability of liquidity-motivated trading in the shares of the firm. The paper theoretically examines the influence of various firm characteristics on the amount of information collected about a firm and on the marginal information content of announcements made by it. Empirical work focuses on the marginal information content of quarterly earnings announcements made by firms. The empirical results are generally consistent with the model's predictions.